Absolute momentum calibration of the HARP TPC - Catanesi, MG; Radicioni, E; Edgecock, R; Ellis, M; Soler, F; Goessling, C; Bunyatov, S; Krasnoperov, A; Popov, B; Serdiouk, V; Tereschenko, V; Di Capua, E; et al. (2008)
In the HARP experiment the large-angle spectrometer is using a cylindrical TPC as main tracking and particle identification detector. The momentum scale of reconstructed tracks in the TPC is the most important systematic error for the majority of kinematic bins used for the HARP measurements of the double-differential production cross-section of charged pions in proton interactions on nuclear targets at large angle. The HARP TPC operated with a number of hardware shortfalls and operational mistakes. Thus it was important to control and characterize its momentum calibration. While it was not possible to enter a direct particle beam into the sensitive volume of the TPC to calibrate the detector, a set of physical processes and detector properties were exploited to achieve a precise calibration of the apparatus. In the following we recall the main issues concerning the momentum measurement in the HARP TPC, and describe the cross-checks made to validate the momentum scale. As a conclusion, this analysis demonstrates that the measurement of momentum is correct within the published precision of 3%. © 2008 IOP Publishing Ltd and SISSA.